Jogja Berhenti Nyaman?: Kepribadian Terang, Kepercayaan pada Perbaikan Diri, dan Penilaian tentang Keadilan Restoratif bagi Pelaku Klitih - Maria Gracia Amara Pawitra; Malvin Geoffrey Cristianto (Asosiasi Psikologi Forensik (Apsifor), 2023)
Klitih has been rampant in Special Regions of Yogyakarta (Daerah Istimewa Yogyakarta) since 2016, targeting people randomly and between groups in conflict. The majority of klitih offenders are underaged who live in unsupportive social environments. They are given juvenile diversion in the context of restorative justice to help them reintegrate and avoid the risk of repeated crimes. However, restorative justice is often challenged by social stigma. This cross-sectional study aimed to examine the role of light triad traits and belief in offender redeemability in determining perceived restorative justice. The data was collected by using Skala Kepribadian Terang, Skala Kepercayaan pada Perbaikan Diri Pelaku, dan Skala Penilaian Keadilan Restoratif. The sample was selected using purposive sampling with inclusion criteria: 1) Indonesian citizens aged 18 years to 60 years, 2) Living in DIY at least since 2016 for at least 2 years, 3) Having updated the news and/discussed klitih cases in DIY. The results of multiple linear regression analysis (N= 124) showed that belief in offender redeemability significantly predicted perceived restorative justice but light triad traits didn’t. This research suggested that offenders should relinquish their delinquent behavior, as well as the public should enhance their belief in offender redeemability and support restorative outcomes. Keywords: Belief In Offender Redeemability; Daerah Istimewa Yogyakarta; Klitih; Light Triad Traits; Perceived Restorative Justice.